Active Commuting to School among Spanish Preschool Children: A Temporal Change Study between 2013 and 2017 - Romina Gisele Saucedo-Araujo; Patricia Gálvez-Fernández; Cristina Cadenas-Sanchez; Mairena Sánchez-López; Pau Avellaneda; Josep M. Suelves; Francisco Javier Huertas-Delgado; Palma Chillón; Manuel Herrador-Colmenero (MDPI AG, 2023)
Background: Active commuting to school may increase the total daily physical activity and achieve health benefits among preschool children. Rates of active commuting to school among Spanish children and adolescents have been widely analysed, while the rates of active commuting to school among Spanish preschool children are unknown. Aim: The main objective of this study was to examine the changes in the rates of active commuting to school in a sample of Spanish preschool children between 3 and 6 years old from 2013 to 2017. Methods: Data were found from five studies carried out across Spain. The study sample comprised 4787 preschool children (4.59 ± 0.77 years old; 51% males). The overall changes in active commuting to school were assessed using multilevel logistic regression analysis. Results: The rates of active commuting to school in Spanish preschool children are around 52%, and the active commuting to school rates have stayed stable throughout the period assessed (odds ratio from 0.40 to 0.58, all p > 0.05). Conclusion: In preschool children, the present study obtained a favourable result on active commuting to school, showing a pattern stability in the examined period similar to other ages. It will be of great importance to promote this behaviour to obtain high levels of active commuting to school.